The Contemporary Christian An Urgent Plea for Double Listening - Stott, John (Stott, John Robert Walmsley) (Leicester Intervarsity Press, 1992)
John Stott urges Christians to listen attentively both to God's ancient Word and to today's world, in order to communicate the authentic gospel.
Keywords: Christian life